Paracoccidioidomycosis prevalence in a public laboratory of the Brazilian unified health system - Carvalhosa, Artur Aburad de; Borges, Fabiano Tonaco; França, Diurianne Caroline Campos; Queiroz, Raíssa Rezende; Moimaz, Suzely Adas Saliba; Garbin, Cléa Adas Saliba (Journal of Oral Diagnosis, 2016)
Paracoccidioidomycosis (PCM) is a systemic fungal disease with oral manifestations that is the most prevalent in Latin America.The purpose of this cross-sectional epidemiological study was to examine the prevalence of PCM in the Public Laboratory (MT Laboratory) of the Brazilian Unified Health System in Mato Grosso. The following data from 3670 cytological and histopathological reports of oral lesions issued by the MT Laboratory over a 4-year (2004–2008) period were analyzed: diagnostic method (oral exfoliative cytology or biopsy), diagnosis by year, origin of cases (urban or rural), and patient gender and age. In the assessment period, 96 cases (2.6%) of PCM were diagnosed. Most cases originated from rural areas (94%), and PCM was the most prevalent in men (97.9%) and in the fifth decade of life (35.4%). These results show that Mato Grosso had a considerable number of PCM cases over a small period, suggesting that this state is an endemic region for PCM in Brazil.